2001
DOI: 10.1084/jem.194.12.1813
|View full text |Cite
|
Sign up to set email alerts
|

The Extracellular Domain of CD83 Inhibits Dendritic Cell–mediated T Cell Stimulation and Binds to a Ligand on Dendritic Cells

Abstract: CD83 is an immunoglobulin (Ig) superfamily member that is upregulated during the maturation of dendritic cells (DCs). It has been widely used as a marker for mature DCs, but its function is still unknown. To approach its potential functional role, we have expressed the extracellular Ig domain of human CD83 (hCD83ext) as a soluble protein. Using this tool we could show that immature as well as mature DCs bind to CD83. Since CD83 binds a ligand also expressed on immature DCs, which do not express CD83, indicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
196
4
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 168 publications
(215 citation statements)
references
References 32 publications
13
196
4
1
Order By: Relevance
“…However, stimulation of naive T cells in the presence of supernatants from CD83-transduced T cell cultures had no significant effect on the proliferative capacity (data not shown) as it was described for sCD83 (20,24,25). Additionally, CD83-transduced T cells and CD4 ϩ CD25 ϩ Treg cells lost their in vitro suppressive capacity in the absence of cell-cell contact (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, stimulation of naive T cells in the presence of supernatants from CD83-transduced T cell cultures had no significant effect on the proliferative capacity (data not shown) as it was described for sCD83 (20,24,25). Additionally, CD83-transduced T cells and CD4 ϩ CD25 ϩ Treg cells lost their in vitro suppressive capacity in the absence of cell-cell contact (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, we have recently shown that inhibition of CD83 expression on DCs by CD83-specific small interfering RNAs leads to a reduced DC-mediated T cell stimulation, indicating that on DCs the membranebound form of CD83 acts as a costimulatory molecule (49). Expression of the undefined CD83 ligand (CD83L) has been suggested on DCs (20) and, recently, on activated CD8 ϩ as well as CD4 ϩ T lymphocytes (49). CD83L was expressed on activated T cells only upon stimulation through CD3/CD28 but not CD3 alone, suggesting that CD83L only functions when T cells are activated in the presence of costimulatory signals provided by CD83 ϩ APCs (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although its exact function is still unknown, various independent studies using soluble forms of CD83 or employing CD83-specific RNA interference provided evidence that this surface molecule is required for efficient DC-mediated T-cell activation [14][15][16][17]19]. Furthermore, it has been shown that CD4 1 single-positive thymocyte development is impaired in CD83 (CD83 À/À ) knockout mice, resulting in pronounced reduction of peripheral CD4 1 T cells [44].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a soluble form of CD83 is detectable at low levels in sera derived from healthy individuals, whereas in contrast, elevated levels are present in patients suffering from certain hematological malignancies [8,11]. Notwithstanding the fact that accumulating experimental evidence suggests that CD83 plays an important functional role in the regulation of DCmediated T-cell-specific immune response [12][13][14][15][16][17][18][19], the exact function of CD83 remains poorly understood [20][21][22]. Nevertheless, various disease-related findings suggest that CD83 holds great potential for future therapeutic application [23].…”
Section: Introductionmentioning
confidence: 99%